Emerging Trends in Vaccine Development Integrating Pharmaceutical Science with Public Health - Mafuts, Vausan (PSPP JOURNALS, 2025)
The rapid evolution of vaccine science accelerated by the COVID-19 pandemic has generated profound shifts in the landscape of global health, biotechnology, and public policy. This study conducts a thematic scoping review to critically examine emerging paradigms in vaccine development, focusing on their scientific innovation, translational pathways, regulatory integration, and public health implementation. Drawing on peer-reviewed literature and strategic policy documents from 2018 to 2025, the analysis identifies four interrelated domains: (1) technological innovation in platforms such as mRNA, saRNA, AI-guided antigen design, and nanocarrier systems; (2) translational pharmacology, including the challenges of real-world implementation, personalized immunization, and genomically-informed vaccinology; (3) policy integration and the tensions between global regulatory architectures, intellectual property regimes, and regional manufacturing autonomy; and (4) public health implementation, where infrastructure, sociopolitical trust, and health equity shape uptake and access. Across all domains, the study finds that scientific progress alone is insufficient to ensure global immunization justice. Instead, the translation of vaccine innovation into equitable impact is mediated by structural inequalities, geopolitical asymmetries, and the uneven capacities of health systems. The findings underscore the urgent need for ethically grounded, interdisciplinary strategies that align biotechnological advancement with equitable public health outcomes, particularly in low- and middle-income contexts.